Rancangan Sistem Informasi Akuntansi Penerimaan Kas Jasa Servis Laptop dalam Meningkatkan Efisiensi Operasional di Sercom Center - Nadhia Rizky Aulia; Febriola Febriola; Meyta Nurul Maulidia; Bela Wulandari; Nurmalasari Nurmalasari (LPPM Universitas Bina Sarana Informatika, 2025)
Sercom Center is a computer store that offers certified used laptops and computer repair services. However, the cash receipt process for service transactions is still handled manually using Microsoft Excel, which leads to issues such as recording errors, delays in accessing customer service data, and inefficiencies in financial reporting. These challenges negatively impact the operational effectiveness and decision-making processes of the management. This study aims to design a web-based accounting information system for cash receipt transactions to enhance the efficiency and accuracy of data recording at Sercom Center. Data collection methods include direct observation, interviews with store administrators, and a literature review of accounting information systems and information technology. The system development follows the waterfall methodology, comprising stages such as requirements analysis, system design using UML (Unified Modeling Language), and the development of a web-based user interface. The result of this study is a functional accounting information system that automates transaction recording, stores service data, and generates structured cash receipt reports in PDF format. The implementation of this system improves operational efficiency, reduces recording errors, accelerates the reporting process, and supports faster and more accurate decision-making.